Stability Analysis of the Flow of Blood in the Branching and Stenoted Arteries - Rotaiyna Essa; Shaimaa Younis (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research is devoted to the stability analysis of the system of equations that describes the flow of blood in the branching and stenoted arteries. This branch takes the form of the character Y, By using the Navier -Stoke of equations in Polar coordinates,when the amplitude is constant and we found that the system is stable under the condition